Online enhancement for the choral classroom - Whiteley, Danette F. (Kansas State University, 2010)
John Dewey once said, “If we teach today as we taught yesterday, we rob our children of tomorrow.” I believe this to be true even in the choral classroom. This paper discusses my philosophy of music education along with ways to incorporate technology into a choral music classroom through the use of web-based resources. As with any educational discipline, technology must be used in the right context to be the most effective. It must be filled with activities, instruction, and guided practice that can pass through the filter of your own philosophy of education and disseminated throughout the Nation Standards in Arts Education.
Keywords: Online enhancement vocal music; Music philosophy; Music (0413)